Pedepsele aplicabile minorilor delincvenți și sancțiuni de drept penal în legea penală a Republicii Moldova [Articol] - Roman, Daniela (CEP USM, 2020)
In the criminal legal doctrine of the Republic of Moldova, the penalty is defined as a sanction of criminal law which consists of a measure of constraint and re-education, provided by law, which is applied to the offender by the court, in order to prevent the commission of new offenses. In a more synthetic, but comprehensive formula, it can be said that the punishment is the specific sanction of the criminal law, the sanction that the judge applies to the one who disobeys a norm of criminal law. The Criminal Code provides that “criminal punishment is a measure of state coercion and a means of correcting and reeducating the convict that is applied by the courts, in the name of the law, to the persons who have committed crimes, causing certain deficiencies and restrictions of their rights.”
THE PENALTIES APPLICABLE TO MINOR OFFENSES AND PENALTIES OF CRIMINAL LAW IN THE CRIMINAL LAW OF THE REPUBLIC OF MOLDOVA
Keywords: pedepse; minori infractori; delincvență juvenilă